The prevalence of obstructive sleep apnea syndrome after COVID‐19 infection - Lin, Wen‐Chun; Wu, Meng‐Che; Wang, Yu‐Hsun; Lin, Che‐Hsuan; Wei, James Cheng‐Chung (Journal of medical virology, 2024)
Obstructive sleep apnea is a well‐known risk factor regarding the severity of COVID‐19 infection. However, to date, relatively little research performed on the prevalence of obstructive sleep apnea in COVID‐19 survivors. The purpose of this study was to investigate the risk of obstructive sleep apnea after COVID‐19 infection. This study was based on data collected from the US Collaborative Network in TriNetX. From January 1, 2020 to June 30, 2022, participants who underwent the SARS‐CoV‐2 test were included in the study. Based on their positive or negative results of the COVID‐19 test results (the polymerase chain reaction [PCR] test), we divided the study population into two groups. The duration of follow‐up began when the PCR test was administered and continued for 12 months. Hazard ratios (HRs) and 95% confidence intervals (CIs) for newly recorded COVID‐19 positive subjects for obstructive sleep apnea were calculated using the Cox proportional hazards model and compared to those without COVID‐19 infection. Subgroup analyses were performed for the age, sex, and race, groups. The COVID‐19 group was associated with an increased risk of obstructive sleep apnea, at both 3 months of follow‐up (HR: 1.51, 95% CI: 1.48–1.54), and 1 year of follow‐up (HR: 1.57, 95% CI: 1.55–1.60). Kaplan–Meier curves regarding the risk of obstructive sleep apnea revealed a significant difference of probability between the two cohorts in the follow‐up periods of 3 months and 1 year (Log‐Rank test, p < 0.001). The risks of obstructive sleep apnea among COVID‐19 patients were significant in the less than 65 year of age group (HR: 1.50, 95% CI: 1.47–1.52), as well as in the group older than or equal to 65 years (HR:1.69, 95% CI: 1.64–1.73). Furthermore, the risks of obstructive sleep apnea were evident in both the male and female COVID‐19 groups. Compared to the control group, the risks of obstructive sleep apnea in the COVID‐19 participants increased in the subgroups of White (HR: 1.62, 95% CI: 1.59–1.64), Blacks/African Americans (HR: 1.50, 95% CI: 1.45–1.55), Asian (HR: 1.46, 95% CI: 1.32–1.62) and American Indian/Alaska Native (HR: 1.36, 95% CI: 1.07–1.74). In conclusion, the incidence of new diagnosis obstructive sleep apnea could be substantially higher after COVID‐19 infection than non‐COVID‐19 comparison group. Physicians should evaluate obstructive sleep apnea in patients after COVID‐19 infection to help prevent future long‐term adverse effects from occurring in the future, including cardiovascular and neurovascular disease.